Prognostic Significance of Admission CRP Levels as a Predictor of Mortality in Burn Patients - Maria Syed; Qaiser Jehangir; Ijaz Hussain Shah; Sana Shaukat Siddiqui; Sara Ishaq; Sarah Zaka (Journal of Rawalpindi Medical College)
Objective: The objective of this study is to evaluate CRP's value as a biomarker of mortality in burn victims admitted to a burn unit.